TEACHERS’ ATTITUDES TOWARD USING AI TOOLS SUCH AS CHATGPT IN ENGLISH LANGUAGE CLASSROOMS IN UZBEKISTAN - Ruzieva Maryam Shuxrat qizi (Modern American Journals, 2026)
The rapid advancement of artificial intelligence technologies has generated significant interest in their pedagogical potential, particularly in foreign language education. Among these technologies, generative AI tools such as ChatGPT have emerged as accessible resources capable of supporting language instruction, material development, assessment, and learner engagement. This study examines teachers’ attitudes toward the use of AI tools, specifically ChatGPT, in English language classrooms within the context of higher education in Uzbekistan. The research is grounded in the understanding that teachers’ perceptions, beliefs, and readiness play a decisive role in the successful integration of innovative technologies into educational practice. The abstract focuses on identifying prevailing attitudes, perceived benefits, concerns, and contextual factors influencing the adoption of AI-assisted tools in English language teaching. Drawing on empirical data collected from English language instructors at philological universities, the study explores how educators evaluate the pedagogical value of ChatGPT in relation to language skills development, lesson planning efficiency, learner autonomy, and academic integrity. Particular attention is given to the balance between perceived instructional support and apprehensions related to ethical use, overreliance on AI, and potential impacts on students’ critical thinking and language production skills. The findings summarized in this abstract indicate that while many teachers demonstrate cautious optimism and recognize AI tools as supportive supplements to traditional instruction, their acceptance is mediated by factors such as digital competence, institutional support, prior experience with educational technologies, and clarity of methodological guidelines. The study contributes to the growing body of research on AI in language education by providing context-specific insights from Uzbekistan and by highlighting the importance of professional development and policy frameworks in shaping informed and responsible AI integration in English language classrooms.
Keywords: Artificial intelligence in education, ChatGPT, English language teaching, teachers’ attitudes, digital pedagogy, higher education, educational technology adoption